Asuhan Keperawatan Keluarga Tn. S Khususnya Pada Ny. S Dengan Hipertensi Di Desa Gunungsari Gatak Rt 02/ Rw 01 Wilayah Kerja Puskesmas Gatak Sukoharjo - Harwin A, Rendy; , Supratman, Ph.D (2015)
Background of study : hypertention is health problem that often occurs in the community, in long time hypertention can lead to heart attack, stroke and heart disease is the leading cause of renal disease. Therefore patient with hypertention should be addresed in order to avoid complex health problems. Goals : in order to gain a real picture of the implementation of the nursing care of hypertention, make data analysis, diagnosis,intervention, and evaluation in medical patient with hypertention. Result : diagnosis that accord with Mr. S family situation is hight risk of perfusion cerebral tissue disruption allied to week knowledge Mr. S family about hypertention and falling hight risk of Mrs. S allied to unability the family about hypertention. Conculation : the family have be able to understanded medical education and be able to take care of the member of the family that have hypertention. Key word : hypertention, fall risk, perfusion cerebral tissue disruption, medical education.